The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/ma0343636
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte Desorption and Exchange Dynamics near the Sharp Adsorption Transition:  Weakly Charged Chains

Abstract: This paper examines the desorption and self-exchange dynamics of polyelectrolyte chains on an oppositely charged surface, in the limit of weak charge, such that the polymer is readily displaced by added ions. The model system adhering to this physically limiting behavior is poly[(dimethylamino)ethyl methacrylate] [PDMAEMA] adsorbing on silica from aqueous solution at elevated pH. Desorption kinetics follow expectations:  a single-exponential decay consistent with a first-order desorption model, with an activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…This corresponds to 14-15 uncompensated positive charges per patch) [66,69]. We have also confirmed that the adsorbed patches are not displaced or transferred during these experiments, nor do they exhibit any lateral mobility [70].…”
Section: Description Of the Systemsupporting
confidence: 76%
See 1 more Smart Citation
“…This corresponds to 14-15 uncompensated positive charges per patch) [66,69]. We have also confirmed that the adsorbed patches are not displaced or transferred during these experiments, nor do they exhibit any lateral mobility [70].…”
Section: Description Of the Systemsupporting
confidence: 76%
“…At this ionic strength for deposition, the Debye length is sufficiently small so that the chains are random coils. Based on a lack of mobility at the conditions of study, we expect that variations in ionic strength during particle capture did not facilitate rearrangements of the adsorbed polymer coils [70,77]. Also, at these deposition conditions, the transport-limited deposition rate has been well-studied by optical reflectometry, so precise timing during the adsorption produces tight (±0.005 mg/m 2 ) control over the density of polymer deposited [65,66].…”
Section: Methodsmentioning
confidence: 99%
“…Coatings stable in a wide range of pH values, concentrations of salts and low molecular mass competitors, and temperatures are formed during the adsorption of ionogenic homopoly mers on oppositely charged surfaces with high charge densities [24][25][26]. As the content of ionogenic groups in the polymer is decreased, the stability of the poly mer coating in water-salt solutions becomes lower: Desorption of the polymer occurs at lower salt con centrations in the surrounding solution [27,28]. A similar picture was observed in [29], in which a reduction in the effective charge of a weak polyelectro lyte macromolecule was attained through a change in the solution pH.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the strong electrostatic attractions between the polycation and the negative silica surface, the pDMAEMA is immobilized on the timescales and conditions in this study. 62, 63 …”
Section: Experimental Descriptionmentioning
confidence: 99%